2017
DOI: 10.1111/imj.13613
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and causes of preoperative anaemia in elective major surgery patients

Abstract: Preoperative anaemia affects 13.9% of patients undergoing elective major surgery. The most common causes are iron deficiency and chronic diseases. The cause was unexplained in 25.5% of patients with anaemia. The prevalence of anaemia in different surgical specialties may have implications on the approach to screening, particularly in resource-limited areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
1
19
1
1
Order By: Relevance
“…With respect to our study on the prevalence of preoperative anaemia among elective major surgery patients, 1 Kearney and To have raised a pertinent point in clinical medicine, that is, the accurate and reliable identification of patients with iron deficiency particularly in the setting of inflammation. 2 Based on the guideline from the Royal College of Pathologists of Australasia, 3 we used serum ferritin <30 μg/L as diagnostic of iron deficiency.…”
mentioning
confidence: 99%
“…With respect to our study on the prevalence of preoperative anaemia among elective major surgery patients, 1 Kearney and To have raised a pertinent point in clinical medicine, that is, the accurate and reliable identification of patients with iron deficiency particularly in the setting of inflammation. 2 Based on the guideline from the Royal College of Pathologists of Australasia, 3 we used serum ferritin <30 μg/L as diagnostic of iron deficiency.…”
mentioning
confidence: 99%
“…4 In the colorectal surgical population (where patients may have impaired iron absorption), preoperative anemia is present in approximately 36% of patients. 4 In the orthopaedic surgery population, a recent Australian study found that 13.9% of patients in an elective surgical cohort were anaemic. 4 These figures mirror the results of another Australian, nationwide audit undertaken by Blood Matters, Victoria, that found 14% of orthopaedic surgery patients to be anaemic.…”
Section: Introductionmentioning
confidence: 99%
“…4 In the orthopaedic surgery population, a recent Australian study found that 13.9% of patients in an elective surgical cohort were anaemic. 4 These figures mirror the results of another Australian, nationwide audit undertaken by Blood Matters, Victoria, that found 14% of orthopaedic surgery patients to be anaemic. 5 These patient groups can be responsible for between 42% and 83% of blood transfusions provided to patients postoperatively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We congratulate Hong et al . for their report on the prevalence and causes of pre‐operative anaemia in elective major surgery.…”
mentioning
confidence: 99%